Ancient Metabolisms of a Thermophilic Subseafloor Bacterium - Smith, Amy R.; Mueller, Ryan; Fisk, Martin R.; Colwell, Frederick S. (Frontiers in Microbiology, 2021)
The ancient origins of metabolism may be rooted deep in oceanic crust, and these early metabolisms may have persisted in the habitable thermal anoxic aquifer where conditions remain similar to those when they first appeared. The Wood-Ljungdahl pathway for acetogenesis is a key early biosynthetic pathway with the potential to influence ocean chemistry and productivity, but its contemporary role in oceanic crust is not well established. Here we describe the genome of a novel acetogen from a thermal suboceanic aquifer olivine biofilm in the basaltic crust of the Juan de Fuca Ridge (JdFR) whose genome suggests it may utilize an ancient chemosynthetic lifestyle. This organism encodes the genes for the complete canonical Wood-Ljungdahl pathway, but is potentially unable to use sulfate and certain organic carbon sources such as lipids and carbohydrates to supplement its energy requirements, unlike other known acetogens. Instead, this organism may use peptides and amino acids for energy or as organic carbon sources. Additionally, genes involved in surface adhesion, the import of metallic cations found in Fe-bearing minerals, and use of molecular hydrogen, a product of serpentinization reactions between water and olivine, are prevalent within the genome. These adaptations are likely a reflection of local environmental micro-niches, where cells are adapted to life in biofilms using ancient chemosynthetic metabolisms dependent on H2 and iron minerals. Since this organism is phylogenetically distinct from a related acetogenic group of Clostridiales, we propose it as a new species, Candidatus Acetocimmeria pyornia.